Pharmacotherapy of Attention Deficit in Neurofibromatosis Type 1: Effects on Cognition - Lidzba, Karen; Granstroem, Sofia; Leark, Robert A.; Kraegeloh-Mann, Inge; Mautner, Victor-Felix (Neuropediatrics, 2014)
Aim Attention deficit with or without hyperactivity (AD[H]D) is a common comorbidity of neurofibromatosis type 1 (NF 1). We tested the hypothesis that permanent medication with methylphenidate can improve cognitive functioning in children with NF 1 and comorbid AD(H)D.Patients and Method We retrospectively analyzed data of a clinical sample of patients with NF 1 with or without AD(H)D, who underwent standardized neuropsychological diagnostics twice (age range: T1, 6–14 years; T2, 7–16 years; mean interval, 49.09 months). A total of 16 children without AD(H)D (nine females) were compared with 14 unmedicated children with AD(H)D (eight females) and to 13 medicated children with AD(H)D (two females). Effects of medication and attention on cognitive outcome (IQ) were tested by repeated measures analysis of covariance (rmANCOVA).Results Medicated children with NF 1 improved significantly in full-scale IQ from T1 to T2 (IQ[T1] = 80.38, IQ[T2] = 98.38, confidence interval [diff]: –25.59 to –10.40, p < 0.0001), this effect was not evident for the other groups. With attention measures as covariates, the effect remained marginally significant.Conclusion Children and adolescents with NF 1 and comorbid AD(H)D may profit from MPH medication regarding general cognition. This effect could be specific for the group of patients with NF 1, and cannot be explained solely by improvements in attention. Controlled, prospective studies are warranted to corroborate our findings.
Keywords: neurofibromatosis type 1; attention deficit; intelligence